El ingreso promedio y el gasto promedio de las personas en el Perú durante el periodo 2017 - 2021 - Chong Ríos, Germán Vladimir (2023)
The welfare of people is measured through average spending; but, an in-depth analysis must investigate the quality and the final destination of it. The approach of this magisterial thesis is oriented to seek the association between the average income and the average expenditure of people in Peru, during the period 2017 - 2021. Guided by this purpose, this research is carried out, classified as Quantitative, of Correlational and non-experimental design. The conclusions reached are: the average income is directly related to the average spending of people, an association validated by means of the statistical test where the Correlation Coefficient was r = 0.98649521 and the Determination Coefficient R2 = 0.97317280. In a complementary way, it can be seen that the main source of the average National Income is Labor, a concept that constitutes 70.32% of the total. On the other hand, investigating the income by geographical area, it can be seen that the highest income occurred in Metropolitan Lima and El Callao, reaching the amount of S/. 1,279.00; coming to far exceed the average national income that is S /. 1,026.00. The second highest income occurred in the Urban Rest area, reaching the figure of S/. 1,070.00. The study of the average expense for the same, reveals that it was concentrated in the Food Consumed Inside the Home group, representing 27.73% of the total.